2021
DOI: 10.1186/s13071-021-05072-y
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerca volvulus transmission in the Mbam valley of Cameroon following 16 years of annual community-directed treatment with ivermectin, and the description of a new cytotype of Simulium squamosum

Abstract: Background The onchocerciasis focus surrounding the lower Mbam and Sanaga rivers, where Onchocerca volvulus is transmitted by Simulium damnosum s.l. (Diptera: Simuliidae), was historically the largest in the southern regions of Cameroon. Annual community-directed treatment with ivermectin (CDTI) has been taking place since 2000, but recent studies have shown that new infections are occurring in children. We aimed to investigate blackfly biting and O. volvulus transmission rates along the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 47 publications
4
27
1
Order By: Relevance
“…Indeed, a stratified analysis including only indigenous households found a crude epilepsy prevalence of 6.7% (14/208) in Bayomen, 6.5% (15/232) in Ngongol and 5.5% (50/905) in Nyamongo [ 26 ]. The high Ov16 seropositivity in children in Bayomen concurs with the results of an entomological study that observed an even higher O. volvulus annual transmission based on blackfly parity and infection rates and transmission potentials in Bayomen (from dissection data) compared to Nyamongo [ 48 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, a stratified analysis including only indigenous households found a crude epilepsy prevalence of 6.7% (14/208) in Bayomen, 6.5% (15/232) in Ngongol and 5.5% (50/905) in Nyamongo [ 26 ]. The high Ov16 seropositivity in children in Bayomen concurs with the results of an entomological study that observed an even higher O. volvulus annual transmission based on blackfly parity and infection rates and transmission potentials in Bayomen (from dissection data) compared to Nyamongo [ 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, in this onchocerciasis focus, CDTI coverage has been sub-optimal. The percentage of infective blackflies in the area was found to be relatively low (0.10–0.36%), but in certain villages extremely high densities of biting blackflies were documented [ 48 ]. Despite a high Ov16 seropositivity in the children, a relatively low epilepsy prevalence (2.6%) was observed in Bayomen.…”
Section: Discussionmentioning
confidence: 99%
“…Around Mount Cameroon, S. squamosum A, C and D occur in sympatry, where hybrids between cytoforms A and C are common [ 18 , 19 ]. Simulium squamosum B has only been found in the Sanaga River [ 18 ] while S. squamosum E2 has recently been described from the Mbam River [ 26 ], a tributary of the Sanaga River.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR was performed using a Rotor Gene Q (Qiagen) with the following cycling conditions: Taq polymerase activation at 95°C for 15 min, 45 cycles of 95°C for 10 s and 61°C for 30 s with fluorescence acquisition on the Fam, Hex and Cy5 channels. In every run, plasmids containing the respective gene sequences were included as positive controls [ 62 ]. A sample was considered positive for a gene if at least one of the three replicates produced a signal while using the 15% outlier removal setting in the Rotor Gene Q Software (version 2.3).…”
Section: Methodsmentioning
confidence: 99%